2019
DOI: 10.5530/ptb.2019.5.20
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Drug Consumption in Emergency Services at North West (Tabuk) Region Hospitals, Saudi Arabia

Abstract: Objectives: This article describes antimicrobial medication use among different age groups and the cost associated with it in emergency department at Northern West (Tabuk) hospitals, Saudi Arabia. The aim of this study to declare the antimicrobial medication use in emergency Units at North West Region Hospitals, Ministry of Health, Saudi Arabia. Methods: It is a 12-month antimicrobial drug consumption by emergency services at North West region hospitals. It included all adults, pediatrics and neonatal populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Thus, Various studies were conducted locally at the hospital in different departments, inpatient, outpatient, emergency, and critical care services to measure antibiotics consumption before the program implementation. [21][22][23] Furthermore, the rational usage of antibiotics at the primary care center. The study randomly selected 25 primary Heather centers and 120 centers in Riyadh city and included all pharmacy staff, pharmacy technicians, and pharmacists to assess knowledge of rational usage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Various studies were conducted locally at the hospital in different departments, inpatient, outpatient, emergency, and critical care services to measure antibiotics consumption before the program implementation. [21][22][23] Furthermore, the rational usage of antibiotics at the primary care center. The study randomly selected 25 primary Heather centers and 120 centers in Riyadh city and included all pharmacy staff, pharmacy technicians, and pharmacists to assess knowledge of rational usage.…”
Section: Discussionmentioning
confidence: 99%
“…Not sure) to Antibiotics misuse decrease sensitivity, Antibiotics can cause secondary infections, if a patient takes antibiotics the patient can be discontinued before the complete course, and the risk of antibiotic resistance is decreased with fewer antibiotic prescriptions. The odd ratio statistically significantly increased (p=0.000) with the answer (No) with Antibiotics can cause allergic reactions with age(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The odd ratio was statistically significantly decreased (p=0.000) with the answer (Not sure) that Antibiotics can cause allergic reactions with age(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), as explored in Table5.…”
mentioning
confidence: 99%
“…[3][4][5] The infection control starting from use necessary infection control measures of hand wishing techniques, using sanitizer or chemical disinfectant and isolation of infected cases, or isolated of cities form to enter and outer from it [3][4][5] Besides, several studies showed resistance bugs locally and overall the world, [6][7][8][9][10] and high consumption of broad spectrum of antibiotics and increased economic burden at emergency, inpatient ward, critical care and ambulatory care services. [11][12][13][14][15][16] Moreover, the pharmacy services consisted of m preparation, distribution and dispensing parenteral or ophthalmic medications. Those pharmacy units need bright places and preparation of sterile products.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are widely used locally and internationally. [1][2][3][4] There is a high consumption of antibiotics, which is the Kingdom of Saudi Arabia, especially in adult patients. Besides, antibiotics consumption was high in neonates and pediatrics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Parental antibiotics most consumption at critical care and inpatient wards units, while the oral antibiotics are widely used at ambulatory care and emergency services. [1][2][3][4] The most antibiotics consumption was a very broad spectrum with the subsequent high economic burden on the healthcare system. [3,4] The parenteral antibiotics need preparation in multiple diluent solutions and various concentration based on local or international guidelines.…”
Section: Introductionmentioning
confidence: 99%